Street vendor sustainability: SMART communication approaches for green innovation - Koswara, Iwan; Komariah, Kokom; Wirakusumah, Teddy Kurnia (Jurnal Kajian Komunikasi, 2023)
Background: Street vendors in Bandung City significantly contribute to economic development and job creation. However, many violate orderliness, cleanliness, and green zonation regulations. To cope with the problem, the Government of Bandung City initiates facilitation to empower the MSME to improve their business values and status and adopt the market development and preferences in terms of digital marketing, environmental friendliness, and green innovation. Purpose: The current research aimed to measure the improvement of street vendors’ capabilities of utilizing communication technology and developing green innovation. Methods: The research used a quantitative approach with a questionnaire spread to the street vendors around the City. It was participated by 89 street vendors. Result: The research demonstrated positive and strong relationships between street vendors’ skill, administration, and saving capabilities as independent variables and innovation as dependent variables. Meanwhile, the independent variable has less relation with innovation, which means they are still dependent on being capable of making green innovation. Conclusion: Referring to the research result, the facilitation and assistance programs should improve street vendors’ business skills, particularly in green practices for innovation. Implications: The research revealed the strong capability of street vendors in using digital communication, such as social media and e-commerce. Nevertheless, further research is required to examine the relationship between digital media and e-commerce capabilities in the adoption of green innovation.